The Perfect Victim: ‘Young girls’, domestic trafficking, and anti-prostitution politics in Canada - Durisin, Elya; van der Meulen, Emily (Anti-Trafficking Review, 2021)
This article explores debates among politicians in Ontario, Canada, regarding anti-trafficking legislation introduced in 2016 and 2017. We find that contemporary discussions in the political sphere have shifted away from concerns about the trafficking of migrant exotic dancers and toward the sexual exploitation of girls and young women, represented as idealised, inculpable victims. We suggest that this conflates the diverse experiences of girls and adult women, configures them all as child-like, and renders both groups as being in need of state protection. The new ‘perfect victim’ serves to legitimise policy approaches that criminalise sexual services, despite those laws being deemed harmful to sex workers in courts and other venues.